2018
DOI: 10.3389/fenvs.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria Inoculation Improves Soil Stability and Fertility on Different Textured Soils: Gaining Insights for Applicability in Soil Restoration

Abstract: Cyanobacteria are ubiquitous components of biocrust communities and the first colonizers of terrestrial ecosystems. They play multiple roles in the soil by fixing C and N and synthesizing exopolysaccharides, which increase soil fertility and water retention and improve soil structure and stability. Application of cyanobacteria as inoculants to promote biocrust development has been proposed as a novel biotechnological technique for restoring barren degraded areas and combating desertification processes in arid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 73 publications
11
107
0
2
Order By: Relevance
“…Biocrusts become more dominant in areas of increasing mean annual temperature and aridity, which could explain why increases in annual temperature, or declines in seasonal precipitation, were associated with positive effects of surface stability on soil multifunctionality, and C, N and P functions. Potential mechanisms accounting for greater stability include physical protection of the surface by lichens and bryophytes, capture of sediment by mosses and greater aggregate stability provided by fungal hyphae and extracellular polysaccharides in cyanobacterial sheath material (Chamizo, Mugnai, Rossi, Certini, & De Philippis, ). Intact surfaces might be expected to have a richer community of biocrust organisms that undertake a greater number of functions associated with mineralization of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Biocrusts become more dominant in areas of increasing mean annual temperature and aridity, which could explain why increases in annual temperature, or declines in seasonal precipitation, were associated with positive effects of surface stability on soil multifunctionality, and C, N and P functions. Potential mechanisms accounting for greater stability include physical protection of the surface by lichens and bryophytes, capture of sediment by mosses and greater aggregate stability provided by fungal hyphae and extracellular polysaccharides in cyanobacterial sheath material (Chamizo, Mugnai, Rossi, Certini, & De Philippis, ). Intact surfaces might be expected to have a richer community of biocrust organisms that undertake a greater number of functions associated with mineralization of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Biocrusts' capacity to fix atmospheric carbon and nitrogen, as well as their role in all other key soil surface properties and processes, is mainly driven by the biomass of photosynthetically active organisms within the biocrust community [14] that have been demonstrated to be one of the best indexes of biocrust development [15,16]. Moreover, it is known that chlorophyll can be used to assess biocrust states in response to seasonal dynamics [17,18], anthropogenic disturbances [19,20], ongoing climate changes [21,22], and restoration activities [23,24]. For all these reasons, large efforts have been devoted during the past decades to obtain reliable measurements of biocrust chlorophyll concentrations [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This crust decreases hydraulic conductivity, limits infiltration, and favors the generation of runoff [82][83][84]. Cyanobacterial colonization on these soils usually enhances microtopography [29,41], improves soil aggregation and stability [22] and increases porosity [85,86], thereby enhancing infiltration. Thus, at the El Cautivo site, increased roughness in the more developed cyanobacterial biocrusts (Cc), in relation to the incipient ones (ICc), (Table 1) surely contributes to facilitate water percolation into the soil [29,41,85].…”
Section: Role Of Cyanobacterial Biocrust In Soil Surface Hydrologymentioning
confidence: 99%
“…In this sense, Miralles-Mellado et al [85] found that pore occurrence in soils covered by cyanobacteria was related to EPS and the ability of filaments to adhere to one another and bind soil particles, and hence affect the soil's spatial organization. Besides, the capacity of cyanobacteria to secrete EPS compounds strongly increases organic carbon content [22,89] and water retention capacity of soils [90]. It has been shown that water holding capacity at field capacity can be 1.2 times higher (on silty loam soils, [31]) or from 2 to 4 times higher (on sandy soils, [85]) in soils with high than with low cyanobacterial cover.…”
Section: Role Of Cyanobacterial Biocrust In Soil Surface Hydrologymentioning
confidence: 99%